Asymptomatic Basilar Artery Plaque Distribution and Vascular Geometry - Kim, Bum Joon (J Atheroscler Thromb, 2019)
Aim: Development of atherosclerotic plaques is affected by vascular geometry and hemodynamics. Hemodynamics in the basilar artery (BA) is unique as the flow converges from vertebral arteries (VAs). Here, we investigated the characteristics of BA plaque based on VA and BA geometry. Methods: Consecutive patients evaluated using high-resolution magnetic resonance imaging (MRI) at a general health center were screened. Geometric characteristics of VA (VA dominancy and VA-BA angles) and BA (BA convexity and BA angles) were assessed. The burden of BA plaques was investigated in each wall (anterior, posterior, left, and right lateral). The characteristics of BA plaques were compared according to VA dominancy (right vs. left), BA angle of lateral view (lateral mid-BA angle; dichotomized), and total plaque burden (divided by tertiles). Results: Of the 1029 subjects, BA plaques were observed in 98 (9.5%) patients, and were more frequently located at the anterior wall (32.4%) and posterior wall (35.0%) than the right wall (15.3%) and left lateral wall (17.6%). Right and left lateral plaques were more frequent in the left and right convex BA, respectively (p = 0.009 and p = 0.024, respectively). Anterior plaques were more frequently observed in low lateral mid-BA angle (p = 0.043). BA plaques were predominant in anterior and posterior walls in patients with lower plaque burden, whereas they were predominant in right and left lateral walls in patients with higher plaque burden (p = 0.001 and p = 0.025, respectively). Conclusions: Asymptomatic BA plaque location was associated with BA convexity and lateral mid-BA angle. The anteriorly and posteriorly located BA plaques may extend to the lateral walls as the plaque burden increases.